The library book - Orlean, Susan (New York : Simon & Schuster, 2018)
Reopens the unsolved mystery of the most catastrophic library fire in American history, the 1986 Los Angeles Public Library fire, while exploring the crucial role that libraries play in modern American culture.
Includes bibliographical references (pages [315]-317)
Keywords: Los Angeles Public Library. -- Central Library -- Fire, 1986.; Los Angeles Public Library. -- Central Library -- History; Public libraries -- California -- Los Angeles -- History; Library buildings -- Fires and fire prevention -- California -- Los Angeles; Fires -- California -- Los Angeles; Arson -- California -- Los Angeles -- History -- 20th century